Optimization of chemical pretreatment for removing cobalt on tungsten carbide substrate using response surface methodology - Shah, A. (Penerbit UTM Press, 2016)
Diamond coating are commonly used in industries especially for application such as cutting tools, biomedical components, optical lenses, microelectronics, engineering, and thermal management systems. The diamond coating quality is strongly depending on substrate preparation prior to diamond coating. Thus, the several process parameters must be studied to obtain optimal parameters which lead high quality diamond coating. In this present work, an attempt was made to optimize pretreatment parameters namely temperature and time on cobalt removal of tungsten carbide. Full factorial experimental designs followed by Response Surface Methodology (RSM) were employed in this study to plan and analyze the experiment. The cobalt removal was the independent response variables. Empirical model was successfully developed to predict amount of cobalt removal on the substrate after single step etching process. Experimental results have shown that the temperature, time and time2 are found to be the most significant factors for cobalt removal. Whereas for interaction of time and temperature were insignificant factors to influence cobalt removal. According to this study, the minimum cobalt content can be obtained at working temperature from 48º to 50ºC for 3 minute.